The layered model of the Copahue geothermal reservoir, Argentina - Barcelona, Hernan (2019)
An exhaustive review of the available data related to the reservoir of the volcano-hosted Copahue geothermal system is presented. Reservoir interpretation to date suggests a vapor-dominated nature. However, the review provided reveals the limitations of this model, regarding the transition from shallow argillic to deep propylitic alteration zones, gas geothermometers calibrated to near-neutral pH environment, production tests, and low recharge of the feed zone, among the other features. We propose that a layered model with a shallow vapor zone above a fluid pressurized reservoir better accounts for the known features of the geothermal reservoir. Temperature profiles define the 800-m-thick upper thermal boundary that includes the impermeable clay cap. An argillic alteration layer (smectite + chlorite + illite + kaolinite) with low electric resistivity response, consistent with the presence of smectite, composes the clay cap. A shallow steam cap develops immediately below the impermeable layer. This vapor zone has 200–215 °C, low seismic activity, and high electrical resistivity, and is highlighted by the isothermal segment of the well logs. The bottom part of the reservoir is subjected to controversy because of the lack of direct measurements. The deep liquid-dominated reservoir has a temperature of ~ 280 °C, develops below 1500 m depth under near-neutral pH condition, and probably has a pervasive propylitic alteration, and wairakite + laumontite + chlorite + epidote + prehnite + actinolite is the likely mineral assemblage. Pressure collapse might trigger the development of the shallow steam cap during deflation–inflation volcanic cycles or Pleistocene-to-recent tectonic deformation. This work points out the main weak points of the previous conceptual model, providing an alternative one based on the first comprehensive compilation of data of the Copahue reservoir. Further research, including a deep exploration drilling stage, is required to establish the physicochemical reservoir state precisely and to validate the proposed layered model.